Narratives and Valuations - Dor Morag; George Loewenstein (Center for Economic Studies and ifo Institute (CESifo), 2023)
While the significance of narrative thinking has been increasingly recognized by social scientists, very little empirical research has documented its consequences for economically significant outcomes. The current paper addresses this gap in one important domain: valuations. In three experiments, participants were given the opportunity to sell an item they owned (mug in Study 1, hat in studies 2 and 3) using an incentive-compatible procedure (multiple price list). Prior to making selling decisions, participants were randomly assigned to either a narrative treatment, in which they were asked to tell the story of their item, or a list treatment, in which they were asked to list the characteristics of their item. The narrative treatment led to significantly higher selling prices and increased rates of participants refusing all offered prices. We further explore potential mechanisms, and the impact of different types of narratives, by analyzing self-reported classifications of, and employing natural language processing techniques on, participants' narratives.
Keywords: 330; decision-making; experimental; narratives; valuations; willingness to accept